Cervical cerclage – a case series of 79 consecutive Shirodkar's sutures over a nine-year period. (18th April 2012) - Siddiqui, I; Akhtar, M; Usman, S; Verma, G; Shabli, S; Young, P
Abstract : Introduction: Prematurity has been the leading cause of perinatal mortality and disability throughout the world and continues to rise despite improvements in care. It is multifactorial and cervical factors may play a part. The RCOG guidelines have questioned the role of cervical suture in preventing mid-trimester loss and preterm labour. Aim: We present a nine year consecutive data of Shirodkar's suture placed by a single operator focussing on maternal and neonatal outcomes, complications and take home baby rates. Methods: All singleton pregnancies with at least one previous mid trimester loss or preterm delivery were included. All the sutures were done by Shirodkar's technique by the same operator and were consecutive between march 2002 and March 2011. Emergency cerclages and those done on multiple pregnancies were excluded. Results: All the included women had history of one or more mid trimester loss or preterm delivery. Twenty-one women had more than one suture put in whereas 6 women had more than one pregnancy with the same suture. Thus of the 79 Shirodkar's sutures placed, 85 pregnancies were achieved. The take home baby rate was 100%. All women received prophylactic antibiotics. Adjuvant therapy in the form of Progestogens, Aspirin, Fragmin or Fish oil was given to selected women, alone or in combination. Discussion: Our Data shows a higher take home baby rate and low maternal complications compared to figures in the published literature. The reasons seam unclear but validates its use in women with a previous mid trimester loss or preterm delivery.